Inovação no registro de procedimentos ambulatoriais de um centro especializado em reabilitação de referência estadual em Mato Grosso - Godoy, Joelma Silva Campos (2024)
The Brazilian state is obligated to take care of the health of people with disabilities. The outpatient procedures performed for this population are recorded through the BPA-I, BPA-C, and APAC data collection instruments by the Specialized Rehabilitation Center, which serves as a state reference in Mato Grosso, and are made available in the Ambulatory Information System of the Unified Health System (SIA-SUS). In the registration process, inconsistencies may occur, which can lead to the rejection of outpatient production and, consequently, the failure to receive payment for the service provided. Thus, the objective of this study is to identify opportunities for improvement in the registration process of outpatient procedures in rehabilitation services for people with disabilities. The methodology is applied and qualitative in nature. As for the technical procedure, it can be classified as bibliographic and documentary, as the basic theoretical development and literature review were based on published materials. The data (numerical) collection was obtained from a secondary source, in this case, SIA-SUS through TABWIN, and organized in EXCEL® spreadsheets. For the discussion and analysis of the results, the integrative review itself was used to carry out the analysis, as it allows a comprehensive and integrated examination of the topic. The study analyzed the availability and quality of outpatient procedure data from 2021 to 2023, revealing significant variations in recorded errors. Recurring issues were identified, such as "error in production data" in APAC and “invalid or mandatory service/classification information in the attendance” in BPA. To improve data quality and reduce errors, continuous training of professionals, process automation, and periodic review of data entry policies and procedures were suggested. The implementation of automatic verification systems, real-time dashboards, and standard operating procedures (POPs) was recommended. Additionally, a system of constant monitoring and immediate feedback should be adopted, with regular meetings to assess and adjust processes, ensuring the sustainability of improvements over time. The improvement proposals resulting from this research could help reduce data registration errors, as well as improve the accuracy of records and enhance the consistency of information. This not only simplifies the workflow but can also improve efficiency.